Concurrent biomineralization of silver ions into Ag0 and AgxO by Leptolyngbya strain JSC-1 and the establishment of its axenic culture. (January 2019) - Khan, Sikandar; Zada, Shah; Ahmad, Shahbaz; Lv, Jing; Fu, Pengcheng
Abstract: Ionic silver is a potential hazard to aquatic life forms because of the increasing usage of silver based materials. The need for developing a sustainable and ecofriendly process to minimize the toxic effects of the free ions burden is now a scientific consensus. Therefore, we report the latest results in cyanobacterium Leptolyngbya JSC-1 investigating the tolerance towards toxic doses of silver, its extracellular biomineralization and silver nano-deposits formation inside the cells, and speculate about potential environmental impacts. In this study, scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS) analysis reveal the extracellular biomineralization of soluble silver (1–100 μM) into corresponding nanoparticles (50–100 nm in diameter) by JSC-1, while X-ray photoelectron spectroscopy (XPS) examination divulged the presence of both Ag + and Ag 0 in extracellularly biomineralized silver, depicting a mixture of both Agx O and elemental Ag. The scanning transmission electron microscopy (STEM), EDS and elemental mapping visualized the formation of intracellular silver nanoparticles. Moreover, this feature of silver tolerance in JSC-1 was further exploited and a novel protocol was developed for isolation and maintenance of axenic culture of this filamentous cyanobacterium. Consequently, this capability of silver biomineralization by JSC-1, both extra- and intra-cellularly might be useful for modeling the Ag resistance mechanism in cyanobacteria and also might be a sustainable alternative for heavy metals bioremediation in aquatic environments. Graphical abstract: Highlights: Metal ions tolerance and biomineralization efficiencies of JSC-1 were explored. Leptolyngbya JSC-1 is capable of biomineralizing Ag + into Ag 0 and Agx O forms. Both extra- and intra-cellular Ag nanoparticles were observed after intoxication. Biomineralized Ag in JSC-1 was exploited for isolation of its axenic culture. It could be an alternative for sustained heavy metals bioremediation of waste water.